Visual Aspects of Lyrical Poems - Malkina, Viktoria (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2020)
The paper is devoted to the issue of the visual in poetry. Visuality is considered here as a feature of the poetics of a verbal text. The author outlines main categories that are necessary for analyzing visuality in a poetic text – first of all, it is the vision (sight) of the lyrical I. The main purpose of the paper is to analyze the principal aspects of the representation of the visual in a lyrical poem. These aspects are: image, lyrical plot, compositional forms and allusions to genres of visual arts. Texts by mainly 20th-century Russian poets serve as material.